Zosteriform herpes simplex: primary infection. - Garofalo, L. (European Journal of Pediatric Dermatology, 2018)
The case described confirms the similarities between HSV and VZV (12) and suggests to research from a clinical and laboratory point of view an etiology of HSV in all cases of herpes zoster, in which a previous varicella is not clearly evident, especially in the early months of life. The zosteriform distribution in HSV infection is an expression of its neurotropism and is reported in the literature both in the case of post-primary and primary infection, but above all it has been studied a lot from an experimental point of view. The zosteriform lesions in primary HSV infection occur after the virus has reached the nervous ganglion during the pathway from the ganglion to the epidermis. Goodpasture (1) showed first that the HSV inoculated in rabbit and guinea pig skin reaches the sensory ganglia via the nerve pathways and then returns to the skin giving zosteriform vesicular eruptions.